Women Education: Emerging Issues and Rethinking - Pati, Jogesh Chandra .et.al.ed (Mittal Publication, 2008)
This is the outcome of research by many educationists and social scientists which focuses on the extent of the development of Women's Education. It looks at the national as well as the regional level, the inequality in the educational level of both the sexes in different spheres of society among different social groups.